Electronically Tunable Triple-Input Single-Output Voltage-Mode Biquadratic Filter Implemented with Single Integrated Circuit Package - Natchanai Roongmuanpha; T. Suesut; Worapong Tangsrirat (Advances in Science Technology and Engineering Systems Journal, 2021)
This article proposes a compact and simple design of electronically adjustable voltage-mode biquadratic filter using fundamental active cell implemented on a single integrated circuit (IC) package as LT1228. The proposed circuit having triple inputs and single output (TISO) employs namely one resistor and two capacitors as the passive components. All the five possible biquadratic filtering responses, namely low-pass (LP), band-pass (BP), high-pass (HP), band-stop (BS) and all-pass (AP), are realized by the appropriate selection of the relevant input signals. The pole angular frequency and the quality factor of the proposed TISO filter are electronically tunable through the bias current of the IC chip LT1228. Nonideal effects and sensitivity performance are carried out. The theoretical results are satisfactorily validated by both PSPICE simulation results and experimental measurements using commercially available LT1228.
Keywords: Analog and Mixed-Signal Circuit Design; Advancements in PLL and VCO Technologies; Digital Filter Design and Implementation